How common are neurocognitive disorders in patients with chronic kidney disease and diabetes? Results from a cross-sectional study in a community cohort of patients in North Wales, UK. Issue 12 (4th December 2018) - Hobson, Peter; Lewis, Aled; Nair, Hari; Wong, Stephen; Kumwenda, Mick
Abstract : Objective: Chronic kidney disease (CKD) affects nearly 9% of global populations and is strongly associated with older age. Neurocognitive disorders (NCDs), which include mild cognitive impairment and dementia, are rising as a result of ageing populations throughout the world. This investigation's aim is to report the frequency of mild to major NCD in a clinical cohort of adults with mild to moderate CKD and diabetes. Setting: Glan Clwyd District general Hospital, North Wales, UK. Participants: We enrolled 178 patients with CKD and diabetes, aged 55 years and over with an estimated glomerular filtration rate <60 >15 mL/min/1.73 m 2, attending a specialist renal and diabetic outpatient clinic. Outcome measures: Frequency of mild and major NCD and the association with the stage of CKD was assessed in all patients attending the specialist clinic. The diagnosis of NCD was based on patient and informant interview, case note review, neuropsychological assessment and application of Diagnostic and Statistical Manual of Mental Disorders version 5. Results: This investigation found 86/178 (48%) of the cohort with an NCD ranging from mild (n=49) to major symptoms (n=37). No association was found with NCD and the stage of CKD. Mild and major NCD was associated poorer outcomes in several cognitive domains, including, language, executive, memory, fluency and attention function (p<0.05). Conclusions: This is the first UK investigation to report that cognitive changes occur in a significant number of older adults with CKD and diabetes. The unexpected finding was that prior to cognitive assessment, not any of the cohort had a pre-existing diagnosis of cognitive impairment, suggesting that the current prevalence and incidence rates of NCD in the general population are possibly significantly underestimated. Our findings also suggest that the cognitive function of patients with CKD should be screened and monitored routinely as part of their overall care management.